Studi Kasus Anak Laki-Laki Usia 8 Tahun Dengan Demam Dengue Derajat I - Yofinda Aurelia Rizkita; Mauliza Mauliza (Lembaga Pengembangan Kinerja Dosen, 2025)
Dengue fever is an acute infectious disease caused by the dengue virus and transmitted primarily by the Aedes aegypti mosquito in urban environments and Aedes albopictus in rural settings. This disease is endemic in many tropical and subtropical regions and is a significant public health concern due to its potentially severe clinical manifestations. This case study presents an 8-year-old boy who was admitted to the hospital with complaints of a high-grade fever lasting for approximately three days. The fever was intermittent and accompanied by chills, which raised suspicions of a viral infection. In addition to fever, the patient also experienced dizziness with a spinning sensation, occasional cough, and flatulence. A thorough clinical evaluation was conducted, including history taking, physical examination, and supporting laboratory tests. Based on the clinical findings and laboratory results, the patient was diagnosed with dengue hemorrhagic fever (DHF) grade I. DHF grade I is characterized by fever, positive tourniquet test, and evidence of plasma leakage without spontaneous bleeding. The patient was managed with supportive therapy, including fluid replacement and close monitoring of vital signs and hematocrit levels to prevent the progression to more severe stages of dengue. No significant complications occurred during the hospital stay. After a period of observation and clinical improvement, the patient was discharged in good condition. This case highlights the importance of early recognition and accurate diagnosis of DHF in pediatric patients, especially in endemic areas. Prompt and appropriate management is essential to prevent complications and ensure recovery. Continuous public health education and vector control remain key strategies in reducing dengue incidence and severity.